When heritage goes ways apart: Heritagization and local involvement at the complex of monuments in Hue, Vietnam - Quyen Mai Le; Girma Kelboro (University of Bonn, Center for Development Research (ZEF), 2019)
This paper is based on the results of qualitative research conducted in Thua Thien-Hue province, Vietnam, between 2017 and 2018. It takes the case of the Complex of Monuments in Hue (hereafter called as The Hue Complex), a heritage site that belonged to the last Feudal Dynasty in Vietnam before 1945. Between the 1970s and 1980s, the Hue Complex and its cultural values was ignored and negatively judged by the contemporary Vietnamese post-socialism regime. Nevertheless, everything changed when the Hue Complex got enlisted by UNESCO as cultural World Heritage site in 1993, and since then it has claimed to be an invaluable cultural property of the nation. This paper aims to understand the heritagization of the Hue Complex and impacts of this process to the local people using the data collected through discourse analysis, in-depth interviews, and focus group discussions. Firstly, it follows the discourses that have been provided in order to transform the Hue Complex from contentious cultural elements of the past into outstanding universal values of the present. The findings show that the heritagization of the Hue Complex involved aesthetic judgments, international and national experts' discourses, and the Vietnamese national grand narratives. Secondly, focusing on the perceptions and experiences of three groups of communities who live in and around the designated sites, we found out that regardless of the attempts of local and national government bodies to synchronize the cultural values of the Hue Complex with global schemes and to promote tourism, the heritage itself is detaching from the local people. They, on the contrary, seem to develop another version of heritage - a spiritual one. These findings suggest nuanced ways of perceiving heritage. They have elucidated the separate processes of heritage making, of which the heritage manufactured and valorized by the dominant actors is different from the heritage as perceived by the local people. Consequently, the enlisted heritage - manifested belong to and benefit for the local community - is eventually losing its meaning and connections with its own people.
Keywords: 330; heritagization; UNESCO; cultural heritage; World Heritage; Hue; Vietnam